Improving the effective use of nitrogen in maize: plant breeding and management perspectives - Palmero, Francisco (My University, 2024)
Over the past 80 years, advances in plant breeding and crop management have increased maize (Zea mays L.) grain yield. However, this increase in maize productivity is linked to a high use of and dependency on nitrogen (N) fertilizers. The high use of N fertilizers can have undesirable environmental consequences. Therefore, improving the effective use of N in maize is critical to reduce its environmental footprint while achieving food security in a climate change context. This dissertation is organized into five chapters (Chapter 1, Introduction, and Chapter 5, Conclusions) addressing plant breeding and management strategies to improve the effective use of N in maize and its productivity. Through four field trials across two locations and four years, Chapters 2 and 3 advance our understanding of how biotechnology-based plant breeding modified carbon (C) and N dynamics in maize. In Chapter 2, we show the effect of extending the expression of a maize MADS-box transcription factor (ZmGos2-zmm28, event DP202216, Corteva Agrisciences) on key physiological and morphological traits associated with C-N dynamics in this crop. We found that the DP202216 trait increased C and N allocation to the grains. These increases were supported by higher accumulation of N in leaves and water-soluble carbohydrates in stems before flowering, along with an improved remobilization after flowering. In Chapter 3, we identify changes in the maximum limit of C and N partitioning to the grains in DP202216 maize hybrids at equal plant growth levels. We also determine the main factors underpinning the mechanisms associated with each observed change in C and N partitioning to grains. The DP202216 plants showed an increase in the upper boundary of C and N allocation to reproductive organs. We showed that this increase in C and N allocation was related to a higher ‘relative’ C and N demand by the grains in the DP202216 hybrids. Finally, in Chapter 4, we analyze different cases of N fertilizer reduction in maize across the United States Corn Belt, considering the uncertainty of "optimal" N rates. We also economically quantify the environmental cost savings to society under the most feasible N rate reduction case. We show that it is feasible to reduce the N fertilizer application while maintaining maize grain yield. This resulted in an increase in farmers’ profit while reducing the environmental costs of the N fertilization practices to society. Taken together, the findings reported in this thesis characterize exciting novel genetic variation for improved N utilization, combined with a practical management tool that could encourage growers to better manage N applications for optimum efficiency in maize production.
Keywords: Corn; Harvest index; Nitrogen harvest index; Sustainability